Clarifying the nexus between Trade Policy Uncertainty, Economic Policy Uncertainty, FDI and Renewable Energy Demand - Md. Qamruzzaman (International Journal of Energy Economics and Policy, 2024)
: As the world becomes increasingly aware of the need to shift towards sustainable energy sources, China and the United States are two global superpowers leading this transition. With growing populations and increasing demand for energy, these countries have recognized the importance of renewable energy in meeting their needs while reducing carbon emissions. The motivation of the study is to evaluate the impact of trade policy uncertainty on renewal energy demean in the USA and China for the period 2000-2021 by employing linear and nonlinear assessment. The test statistics derived through the cointegration test by following Bayer-Hancked and Makki's cointegration established a long-run tie in the empirical equation. Moreover, the long-run linkage was revealed with symmetry and asymmetry investigation. Referring to the coefficients of linear assessment, the study established that uncertainties have a detrimental role in clean energy demand in the long- and short-run assessment. The asymmetric association between uncertainties and REC has been documented through the execution of a standard weld test with the null of symmetry. The directional causality test established a unidirectional linkage between trade policy uncertainty and REC [TPU<- ->REC], and a bidirectional linkage between economic policy uncertainty and REC [EPU<- ->REC].